PENGARUH STRATEGI PEMBELAJARAN THINK PAIR SHARE DAN SELF CONTROL TERHADAP HASIL BELAJAR FIKIH SISWA - Yusri, Muhammad; Ananda, Rusydi; Haidir, Haidir (UIN Sumatera Utara Medan, 2023)
Many factors that determine success in the learning process are interrelated. These factors are: teachers, students, curriculum, learning, media, infrastructure and environment. The teacher's role is to design learning strategies that can make students always study well and enthusiastically. Such a learning strategy will have a positive impact on achieving optimal learning achievement. This research aims to determine: (1) the learning outcomes of students' Jurisprudence taught using the TPS learning strategy with expository learning strategies, (2) the learning outcomes of Jurisprudence students with different self-control, and (3) the effect of learning strategies and self-control on learning outcomes Student Fiqh. The research was conducted at Madrasah Aliyah Al-Washliyah, Lima Puluh Pesisir District, Batubara Regency. This research method is a quantitative research with quasi-experimental research methods. The research population is 3 classes with a sample of 1 research class as the experimental class and 1 class as the control class. Data collection instruments were multiple choice test and questionnaires were given to students who were research respondents, then data analysis techniques were two-way analysis of variance. The research findings show: (1) the average Jurisprudence learning outcomes of students taught using the think pair share learning strategy is higher than the average Jurisprudence learning outcomes of students taught with expository learning strategies. Thus the think pair share learning strategy is more effectively applied in Jurisprudence learning in order to improve students' Jurisprudence learning outcomes without paying attention to differences in self-control, (2) the average learning outcomes of students with high self-control who are taught using the think pair share learning strategy and expository learning strategies are higher than the average learning outcomes of students with low self-control, and (3) there is the influence of learning strategies and student self-control which have a different effect on learning outcomes of Jurisprudence. In connection with the findings of this study, it can be recommended for teachers to implement the think pair share learning strategy. Through the implementation of the think pair share learning strategy, it is hoped that teachers can arouse and motivate students' involvement and active participation in learning